2018
DOI: 10.35790/ecl.6.2.2018.21993
|View full text |Cite
|
Sign up to set email alerts
|

Gambaran Ketajaman Penglihatan terhadap Lama Penggunaan dan Jarak Pandang Gadget pada Siswa Kelas XII SMA Negeri 9 Binsus Manado

Abstract: Deterioration of visual acuity commonly occurs among students. This study was aimed to obtain the profile of visual acuity related to duration of gadget usage and distance between eye and the gadget among XII grade students of SMA Negeri 9 Binsus Manado (senior high school). This was a descriptive study. There were 105 students as subjects in this study; 34 of them (32.38%) had decreased visual acuity. There were 80 subjects (76.19%) that did not wear glasses, consisted of 27 males (25.72%) and 44 females (41.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
0
0
1
Order By: Relevance
“…Previous research found that there was a connection between the use of gadgets and a decrease in visual acuity, where the use of gadgets was one of the factors causing a decrease in visual acuity in junior high school students in the Rappocini District, Makassar City. where the higher the use of gadgets, the higher the risk of eye health problems among students [2], [12], [14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research found that there was a connection between the use of gadgets and a decrease in visual acuity, where the use of gadgets was one of the factors causing a decrease in visual acuity in junior high school students in the Rappocini District, Makassar City. where the higher the use of gadgets, the higher the risk of eye health problems among students [2], [12], [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, if you don't pay attention to time limits when using them, close distances and the wrong position can affect eye health. Many school-aged children currently suffer from eye health problems due to the negative impacts of using gadgets [2], [3], [6], [7].…”
Section: Introductionmentioning
confidence: 99%
“…Namun pembelajaran daring mengharuskan anak menggunakan media elektonik sebagai perangkat pendukung pembelajaran. Dalam hal ini anak harus berada di depan media elektronik atau gagdet terus merus [3]. Kondisi ini dapat berdampak pada kesehatan penglihatan anak.…”
Section: Pendahuluanunclassified
“…Penelitian terdahulu menunjukkan ada hubungan antara jarak dan lama menggunakan gadget dengan gangguan visus (tajam penglihatan) namun tidak terdapat hubungan bermakna antara posisi penggunaan gawai dengan gangguan visus pada anak SMA di Kawangkoan (Sumakul & Marunduh, 2020). Sedangkan penelitian Richter (Richter et al, 2018) di salah satu SMA di Manado didapatkan pada umumnya lama penggunaan gadget ≥2 jam dengan jarak pandang gadget <30 cm dan tidak didapatkan perubahan visus yang nyata setelah 30 hari. Skrining awal adanya gangguan tajam penglihatan bermanfaat untuk anak segera dapat penanganan seperti penggunaan alat bantu kaca mata yang sesuai.…”
Section: Pendahuluanunclassified